PERENCANAAN DAN AKTUALISASI KURIKULUM DI SEKOLAH BERBASIS INKLUSI - Ummah, Aminatul (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The research based on the existence of inclusive-based schools that receive students who have special needs to study together in the regular class. Every people has equal right in education so that the government socializes for each region to have a child-friendly inclusion school with student who have special needs. Curriculum and learning are the main foundations of educational success, therefore researchers focus on curriculum management and learning in inclusive-based schools.The focus of this research is learning and Curriculum management in inclusive school. The method used in this research is qualitative approach with multi case design, data source is taken from person, place, and paper with primary and secondary data source. Data collection techniques are participative observation, indept interview, and documentation. The results showed (1) curriculum and learning planning used in grassroots approach inclusion-based schools; Doing assumptions on students with special needs; Designing individual learning programs (PPIs); Using humanistic curriculum design model; Learning classroom management using pure inclusion model and special class; (2) curriculum and learning Actualization in inclusive-based schools using a modified curriculum from the curriculum of the education nation ; The content of learning emphasizes life-skills; Instructional design used dick cery design; Using the method of ABA therapy (Applied Behavior Analysis); Learning refers to individual learning programs of students with disabilities;